THE PURCHASE DECISION IN VIEW OF BRAND EQUITY, HEALTHY LIFESYTLE, AND BRAND AMBASSADOR (Study on Lemonilo Noodle Consumers in Pasar Kliwon Surakarta Sub-district) - Putri Deta Prasetyanti; Bambang Mursito; Istiqomah Istiqomah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The objective of this investigation is to explain the impact of brand equity, healthy lifestyle, and brand ambassador on decisions of purchasing for Lemonilo Noodles in Pasar Kliwon Surakarta Sub-district. This research applied quantative descriptive approach. The subject of this investigation is Lemonilo Noodles Consumers in Pasar Kliwon Surakarta Sub-district within period of 3 months with a samples of 100 respondents according to the 2014 Ferdinand formula. Non-probability sampling was utilized in this investigation and purposive sampling was used to determine the sample size. A likert scale was used to collect data. Using the classical assumption test, multiple linear regression analysis model, the t-test, and the coefficient of determination. This study demonstrates that there is a positive and significant influence on brand equity, healthy lifesytle, and brand ambassador variables. The coefficient determination test yielded an Adjusted R Square value of 0,664 indicating that brand equity, healthy lifestyle and brand ambassador variables influence the purchase decision of lemonilo noodles in Pasar Kliwon Surakarta Sub-district, while other variables explain the remainder. Keywords: Brand Equity, Healthy Lifestyle, Brand Ambassador, and Purchace Decision